DOA DAN HARAPAN AKAN ALLAH YANG MEMBEBASKAN SEBUAH TAFSIRAN POST-KOLONIAL DANIEL 9:1-27 - Nefry Christoffel Benyamin (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2019)
This writing tries to interprete one of the chapters in the Book of Daniel, especially Daniel 9:1-17 by using post-colonial perspective. The perspective invites the readers to realize that they inherited the values from the colonialization time and therefore they need to re-think critically the interpretation of biblical texts which are fulfilled by the values of colonialism. Daniel 9:1-27 talks about God’s hope that makes His people to experience God’s freedom. Based on the texts above, the writer makes reflections about its meaning and tries to apply it in the context of the Church in the present situation.